2008
DOI: 10.3174/ajnr.a1375
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of the Human Red Nucleus in the Brain Resting State at 3T

Abstract: BACKGROUND AND PURPOSE:Previous structural data obtained with diffusion tensor imaging axonal tracking have demonstrated possible in vivo connections between the human red nucleus (RN) and the sensorimotor and associative cortical areas. However, tractographic reconstructions can include false trajectories because of, for instance, the low spatial resolution of diffusion images or the inability to precisely detect fiber crossings. The rubral network was therefore reassessed by functional connectivity during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 43 publications
9
64
0
Order By: Relevance
“…Although the high resolution of our new scanner may positively affect the counting in the deep brain structures, it is unlikely to affect the correlation among the deep brain structures. Our results were in line with the previous investigations using a high-resolution ECAT HRRT scanner (CTI/Siemens) (9) and functional MR imaging (fMRI) (5). Unlike the previous investigation, however, our study revealed functional correlations between the RNs and association cortices.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although the high resolution of our new scanner may positively affect the counting in the deep brain structures, it is unlikely to affect the correlation among the deep brain structures. Our results were in line with the previous investigations using a high-resolution ECAT HRRT scanner (CTI/Siemens) (9) and functional MR imaging (fMRI) (5). Unlike the previous investigation, however, our study revealed functional correlations between the RNs and association cortices.…”
Section: Discussionsupporting
confidence: 92%
“…The current report is, to our knowledge, the first to reveal metabolic correlation between RNs and other brain regions. Using an fMRI, Nioche et al investigated a similar functional association between RNs and other cortical structures and suggested possible networks in which the RNs and the cerebral association areas are involved (5). The results of the present study are in line with theirs from the standpoint that the RNs had a functional network with associative cortical and limbic areas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This approach has recently helped to clarify the functional connectivity of several brain regions, including the thalamus [21], insula [22], striatum [23], anterior cingulate cortex [24], red nucleus [25], cerebellum [26], and amygdala [27]. These findings have been shown to be consistent with meta-analyses of human functional imaging data [28,29] and anatomical data from humans [30,31], non-human primates [32] and rodents [33].…”
Section: Introductionsupporting
confidence: 75%
“…There is at least one system involved in salience and executive control of which the claustrum is an integral part, and that is the rubral network based on the red nucleus. This consists, in addition to the red nucleus, the cerebellum, mesencephalon, substantia nigra, hypothalamus, pallidum, thalamus, insula, claustrum, posterior hippocampus, precuneus, and occipital, prefrontal, and fronto-opercular cortices (Nioche et al, 2009). Little is known about the functions of this circuit.…”
Section: The Saliency Detection Hypothesismentioning
confidence: 99%